Stres Berhubungan dengan Kejadian Pityriasis Sicca (Ketombe) pada Mahasiswa Fakultas Kedokteran Universitas Muhammadiyah Semarang - Amiroh, Ellya Umi; Krisnarto, Eko; Ratnaningrum, Kanti (Jurnal Kesehatan Andalas, 2024)
Pityriasis sicca is a common problem in Indonesian society that can be caused by various factors and the main cause is the fungus Pityrosporum ovale which causes rough and smooth scales. Objective: To prove the relationship between the degree of stress, age and gender with the incidence of Pityriasis sicca (dandruff) in students at the faculty of medicine Muhammadiyah University Semarang. Methods: This research used a cross-sectional design with a purposive sampling technique on students class of 2023 from the faculty of medicine at Muhammadiyah University Semarang. Primary data was obtained through filling out questionnaires and physical examination of respondents. Analysis of the age variable was carried out using the Mann-Whitney test and the gender and degree of stress variables used the Chi-square test. Results: From 112 respondents, it was found that age was not related to the incidence of Pityriasis sicca in students at the faculty of medicine Muhammadiyah University Semarang (p=0.185). Gender was not related to the incidence of Pityriasis sicca (p= 0.899). The degree of stress was related to the incidence of Pityriasis sicca (p=0.000). Conclusion: The degree of stress is related to the incidence of Pityriasis sicca, while age and gender are not related to the incidence of Pityriasis sicca.          Keywords:  dandruff, Pityriasis sicca, stress levels